Distribution of 200m individual medley speed based on the principle of speed coefficient - Zhang, Z.; Zheng, W.; Ma, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: This paper studies the characteristics of the 200m individual medley event. The study examined characteristics of the total swimming race, including speed distribution and an analysis of the differences with world elite athletes. Study findings will provide some suggestion for the training for the 2008 Olympic Games for performance improvement.